Модель підготовки майбутніх учителів початкових класів до реалізації фахових компетентностей в інклюзивному освітньому просторі - Акімова, Олена (My University, 2024)
Предметом статті виступає презентація складових елементів структурно-функціональної моделі підготовки майбутніх учителів початкових класів до реалізації фахових компетентностей в інклюзивному освітньому просторі. Розкриваються основні складові підготовки майбутніх учителів початкових класів до реалізації фахових компетентностей в інклюзивному освітньому просторі в блоках: методологічному, цільовому, теоретичному, змістовно-організаційному, діагностично-рефлексивному; містить критеріальний апарат оцінювання ефективності моделі системи підготовки майбутніх учителів початкових класів до реалізації фахових компетентностей в інклюзивному освітньому просторі; визначено зміст мотиваційно-цільового, когнітивного, організаційно-функціонального, контрольно-оцінного компонентів моделі системи підготовки майбутніх учителів початкових класів до реалізації фахових компетентностей в інклюзивному освітньому просторі. Охарактеризовано змістове тематичне наповнення освітніх компонентів професійного циклу підготовки, що презентують на різноманітних рівнях здобуття освіти: «Інклюзивна освіта», «Організаційні засади діяльності асистента вчителя», «Філософія інклюзивної освіти». The subject of the article is the presentation of the constituent elements of the structural-functional model of training future primary school teachers for the realization of professional competences in an inclusive educational space. The main components of the training of future primary school teachers for the implementation of professional competences in the inclusive educational space in the blocks are revealed: methodological, target, theoretical, content-organizational, diagnostic-reflexive; contains a criterion apparatus for evaluating the effectiveness of the system model for training future primary school teachers for the implementation of professional competences in an inclusive educational space; the content of motivational-targeted, cognitive, organizational-functional, control and assessment components of the model system for training future primary school teachers for the realization of professional competences in an inclusive educational space. The meaningful thematic content of the educational components of the professional training cycle presented at various levels of education: «Inclusive education», «Organizational principles of the activity of a teacher's assistant», «Philosophy of inclusive education» is haracterized. The preparation of future primary school teachers for the implementation of professional competences involves the implementation of the following principles: fundamentalization of education; professional orientation; digitization of professional training; personal humanization; pedagogical determinism; regionalism; an open undefined personality; educational inclusion.The predicted result of the model of the system of professional training of future primary school teachers for the realization of rofessional competences in an inclusive educational space is included in the diagnostic-reflexive block and characterized as: formation of the readiness and ability to prepare future primary school teachers for the implementation of professional competences in an inclusive educational space during professional training.
Keywords: фахові компетентності; інклюзія; інклюзивна освіта; освітній процес; дитина з особливими освітніми потребами; professional competences; educational process; inclusion; inclusive education